1996
DOI: 10.5144/0256-4947.1996.249
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumothorax: A Retrospective Study of Twenty-Five Patients and Literature Review

Abstract: We present a retrospective study of 25 patients with spontaneous pneumothorax (three recurrent), comprising 16 Saudis (nine males and seven females) and nine non-Saudis (eight males and one female), seen at the Asir Central Hospital, Abha, over a period of 45 months. Almost one-third of the patients (9/25) had no underlying cause discernible by our investigational facilities (chest x-ray, ultrasonography, computed tomographic scan, and flexible bronchofiberscopy). Underlying pneumonia (three patients), pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Furthermore, the results showed that the highest proportion of patients were diagnosed with left PSP (43.5%), followed by right PSP (38.9%). This contradicts a previous study conducted with 25 patients in Saudi Arabia, which found that the ratio of right-to-left pneumothorax was 6:1, with only one bilateral pneumothorax documented [ 22 ]. Moreover, PSP recurrence was observed in 42% of sampled patients, with at least one recurrence for patients diagnosed with bilateral-simultaneous PSP.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the results showed that the highest proportion of patients were diagnosed with left PSP (43.5%), followed by right PSP (38.9%). This contradicts a previous study conducted with 25 patients in Saudi Arabia, which found that the ratio of right-to-left pneumothorax was 6:1, with only one bilateral pneumothorax documented [ 22 ]. Moreover, PSP recurrence was observed in 42% of sampled patients, with at least one recurrence for patients diagnosed with bilateral-simultaneous PSP.…”
Section: Discussioncontrasting
confidence: 80%
“…In one study, smoking increased the rate of developing PSP by 22-fold in males [ 21 ]. Previous findings in Saudi Arabia revealed that 62% of PSP patients were smokers [ 12 ], but to the contrary, another study reported that smoking was documented in only 16% of patients [ 22 ]. It is worth noting that these two studies used a small number of sample patients.…”
Section: Discussionmentioning
confidence: 99%